2007
DOI: 10.3200/socp.147.6.681-706
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and Explicit Prejudice Toward Overweight and Average-Weight Men and Women: Testing Their Correspondence and Relation to Behavioral Intentions

Abstract: The authors examined prejudice toward overweight men and women. Participants (N = 76) indicated their perceptions, attitudes, behavioral intentions, and implicit associations toward an average-weight or overweight man or woman. Results indicated the presence of explicit and implicit antifat prejudice, with male participants showing greater negativity toward overweight targets. Analyses of covariance indicated that overweight targets received greater derogation than did their average-weight counterparts, regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
87
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 43 publications
13
87
0
3
Order By: Relevance
“…We found a correlation of r = 0.22. This is consistent with previous research (Brochu & Morrison, 2007).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We found a correlation of r = 0.22. This is consistent with previous research (Brochu & Morrison, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…Implicit measures are designed to tap into people's attitudes that are automatically activated by the attitudinal object and thus less subject to distortion (Teachman, Gapinski, Brownell, Rawlins, & Jeyaram, 2003). Previous research on the relationship between implicit and explicit attitudes measures has been equivocal (Brochu & Morrison, 2007). It is important to consider which measure is a better predictor of discriminatory behaviors.…”
Section: Weight Biasmentioning
confidence: 99%
“…Specifically, one study showed the health professionals have an implicit anti-fat bias, and they also endorse negative stereotypes about heavy individuals [37]. Others have shown that relatively few differences emerge between individuals implicit and explicit associations toward weight [38]. For many other stigmas such as race, implicit and explicit attitudes differ such that negative explicit attitudes are not expressed [e.g.…”
Section: Additional Approachesmentioning
confidence: 99%
“…Hausmann & Ryan, 2004), and prejudice against the overweight and obese (e.g. Brochu & Morrison, 2007).…”
Section: Limitations To Rationalitymentioning
confidence: 99%